SYNTHESIS, MOLLUSCICIDALAND ANTIMICROBIAL POTENTIALITIES OF IRON TRIAD MONONUCLEAR METAL COMPLEXES INCORPORATING TRIDENTATE ASYMMETRICAL SCHIFF BASE LIGANDS CONTAINING SOFT SULFUR COORDINATING ATOM - M ALOSAIMI, AMAL; EL MANNOUBI, INES; A ZABIN, SAMI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This work aimed at synthesizing tridentates asymmetrical Schiff base ligands containing sulfur atom and using them for preparing metal complexes with the iron triad metals. The prepared compounds were assayed in vitro for antimicrobial potential and in vivo molluscicidal activity. Methods: The unsymmetrical tridentate Schiff bases (SL1, SL2, and SL3) were prepared using 2-aminothiophenol as primary amine and condensed with 2-carboxybenzaldehyde, 2-hydroxy-1-naphthaldehyde, and 7-formyl-8-hydroxyquinoline. These ligands were used in preparing metal complexes with iron triad metals. The synthesized Schiff base ligands and their corresponding metal complexes were characterized and their proposed structures were confirmed using different physical and spectroscopic analytical techniques. All ligands and their corresponding metal complexes were assayed against different bacterial and fungal strains using the agar disk-diffusion technique. The molluscicidal activity was performed according to the standard reported methods as cited in the literature and by observing the toxicity and lethal dose according to the WHO guidelines. Results: The synthesized ligands behave as tridentate (NOS) ligands and form mononuclear complexes with the general formula [M(SL)2] with an octahedral geometry around the central metal ion. Metal complexes were non-electrolytic in nature. The in vitro antibacterial and antifungal examination results showed weak activity of the ligands, and there was enhanced activity with the complexes. The in vivo molluscicidal activity of the tested compounds showed good activity. Conclusion: The targeted compounds were prepared successfully, characterized, and showed some biological activity but lower than the standard reference drugs.